Changes in Socio-Economic and Cultural Behavior of Female Indonesian Migrant Workers - Sukesi, Keppi; Setyowati, Endang; Wahyuningtyas, Agustina Shinta Hartati; Baladina, Nur (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2017)
Indonesian Migrant Workers (BMI) is a development hero that contributes to reducing the national poverty rate; however, the departure of BMI abroad has an impact on the change of BMI and their families. This study aims to analyze the changes that occur in the socio-economic and cultural sectors. The results showed that there was a change of socio-economic and cultural behavior of full-time BMI women in the village of Majangtengah after they returned to the area of origin. Social change occurs in the family to the community. At the family level there is a change in the structure and function of the family because of the absence of a mother in the household. The core family structure is transformed into a widespread family, with no mother, the BMI who joins the family of origin. The second structure is to survive with the core family minus the mother, or father to be single parent. The third form is the children living alone at home because there is no parent or relative guarding.